2006
DOI: 10.1109/lgrs.2005.858485
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Fire Severity: Assessing the Performance of the Normalized Burn Ratio

Abstract: Several studies have used satellite data to map different levels of fire severity present within burned areas. Increasingly, fire severity has been estimated using a spectral index called the normalized burn ratio (NBR). This letter assesses the performance of the NBR against ideal requirements of a spectral index designed to measure fire severity. According to index theory, the NBR would be optimal for quantifying fire severity if the trajectory in spectral feature space caused by different levels of severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
201
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(246 citation statements)
references
References 18 publications
7
201
1
12
Order By: Relevance
“…Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option. The limitations of NBR for immediate post-fire assessment were already pointed out by Roy et al [76].…”
Section: Summary Of Results Which Si Should We Choose?mentioning
confidence: 87%
“…Although NBR is often considered the best SI for burned area mapping short time after fire and therefore widely used for burn severity assessments [7,19,21,23,[27][28][29], our results demonstrated that in certain vegetation types other SI would offer a better option. The limitations of NBR for immediate post-fire assessment were already pointed out by Roy et al [76].…”
Section: Summary Of Results Which Si Should We Choose?mentioning
confidence: 87%
“…Band 7 is sensitive to the cellulose content and water content of the plants, and increases with greater cover of soil, ash, or carbon [7]. In forested systems Band 7 increases with higher burn severity [7] but may decrease with burn severity in grass dominated systems [22]. In forested systems recent burns have negative NBR values (R4 < R7) whereas unburned vegetated has strongly positive NBR values (R4 > R7).…”
Section: Remotely Sensed Burn-severity Indicesmentioning
confidence: 99%
“…Overall, correlations with field-based data and classification accuracies of the indices are good, but do seem to vary among regions; of the 26 studies using dNBR reviewed by French et al [9] the average classification accuracy was 73% but accuracies varied from 50 to 95%. Also, because the two spectral bands do not change at the same rate with increased burn severity, NBR, by itself, does not meet the criteria for being an "optimal index" for assessing burn severity [22]. Other remote-sensing methods, such as spectral-mixture analysis, have also shown promise for detecting burn severity and post-fire effects [26], but field evaluation of these methods have been limited in geographic scope compared to dNBR and RdNBR.…”
Section: Remotely Sensed Burn-severity Indicesmentioning
confidence: 99%
“…However, remote sensing methods have limitations that can cause errors in final burned area products [19]. Major factors include the presence of clouds, which significantly reduces the ability to detect a fire hotspot due to the attenuation of the spectral radiance emitted by the flaming and smoldering phases in the biomass burning process [20], the lack of data on the moment of fire occurrence and, especially, the incompatibility of the spatial resolutions of some sensors, making these sensors unsuitable for the identification of fires [21][22][23].…”
Section: Introductionmentioning
confidence: 99%